Protective Potential of Montelukast Against Hepatic Ischemia/Reperfusion Injury in Rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; DULUNDU, ENDER; ERCAN, FERİHA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2010)
Ischemia and reperfusion (I/R) injury is characterized by significant oxidative stress, characteristic changes in the antioxidant system and organ injury leading to significant morbidity and mortality. This study was designed to assess the possible protective effect of montelukast, a selective antagonist of cysteinyl leukotriene receptor 1 (CysLT1), on hepatic I/R injury in rats. Wistar albino rats through clamping hepatic artery, portal vein, and bile duct, were subjected to 45 min of hepatic ischemia followed by 60 min reperfusion period. Montelukast (10 mg/kg; i.p.) was administered 15 min prior to ischemia and immediately before reperfusion period. At the end of the reperfusion period, the rats were killed by decapitation. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) activity, and proinflammatory cytokines (TNF-alpha and IL-1 beta) were determined in blood samples. Malondialdehyde (MDA), and glutathione (GSH) levels and myeloperoxidase (MPO) and Na+, K+-ATPase activities were determined in the liver tissue samples while formation of reactive oxygen species was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probes. Tissues were also analyzed histologically. Serum ALT, AST, and LDH activities were elevated in the I/R group, while this increase was significantly decreased by montelukast treatment. Hepatic GSH levels and Na+, K+- ATPase activity, significantly depressed by I/R, were elevated back to control levels in montelukast-treated I/R group. Furthermore, increases in tissue luminol and lucigenin CL, MDA levels, and MPO activity due to I/R injury were reduced back to control levels with
Keywords: leukotrienes; montelukast; ischemia/reperfusion; liver; myeloperoxidase; cytokines; ISCHEMIA-REPERFUSION INJURY; RECEPTOR BLOCKER MONTELUKAST; TISSUE-INJURY; FREE-RADICALS; LIVER; LEUKOTRIENES; ANTIOXIDANT; CELLS; DEHYDROGENASE; GLUTATHIONE